2009
DOI: 10.1111/j.1365-2672.2009.04157.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities of tyre monofill sites: growth on tyre shreds and leachate

Abstract: Aims:  To investigate bacterial communities of tyre monofill sites, colonization of tyre material by bacteria and the effect of tyre leachate on bacteria. Methods and Results:  Culturable bacteria were isolated from buried tyre shreds and identified using fatty acid methyl ester analysis. Isolates belonged to taxonomic groups such as Bacilli, Actinobacteria, Clostridia, Flavobacteria, β and γ‐proteobacteria. For tyre material colonization experiments, Bacillus megatarium, Bacillus cereus, Hydrogenophaga  flava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Actinobacteria was found in the D r a f t soil and groundwater samples from both sites but not in the leachate samples. This was not expected as Actinobacteria has previously been found in leachate samples (Vukanti et al, 2009).…”
Section: Dominant Phyla and Genera In Both Sitescontrasting
confidence: 49%
See 2 more Smart Citations
“…Actinobacteria was found in the D r a f t soil and groundwater samples from both sites but not in the leachate samples. This was not expected as Actinobacteria has previously been found in leachate samples (Vukanti et al, 2009).…”
Section: Dominant Phyla and Genera In Both Sitescontrasting
confidence: 49%
“…Proteobacteria were most dominantly found in leachate samples from landfills (Song et al, 2015a, Song et al, 2015b and aquifer sediments (Wan et al, 2012). It has been reported that members of Proteobacteria involved in the degradation of aromatic oils such as polycyclic aromatic hydrocarbons (Vukanti et al, 2009). These bacteria have been found to lose dominance in older leachate samples (Köchling et al, 2015) and they were detected at highly abundant levels in aged refuse from Shanghai landfills (Xie et al, 2012).…”
Section: Dominant Phyla and Genera In Both Sitesmentioning
confidence: 97%
See 1 more Smart Citation
“…Table 11. Tire rubber reclaiming/devulcanization processes [41,46,47] . SEM photomicrographs of A) tensile fractured surface of NR-PBR/RTR blends with different RTR loading [72]; B) tensile fractured surface of NR/GTR and NR/RTR (30phr) [79] C) tensile fractured surface of SBR/GTR and SBR/RTR (30phr) [80]; D) Abrasion pattern on SBR and 30phr GTR filled SBR [69].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…RTR is also favored when blending with rubber as the miscibility of the RTR/rubber blends are reported to be better compared GTR/rubber blends (Li et al, 2005, Balasubramanian, 2009, Rooj et al, 2011. Table 2.4 Physical, chemical and microbial processes of tire rubber reclaiming/devulcanization (Myhre et al, 2012, Vukanti et al, 2009, Shah et al, 2013, Shi et al, 2014 …”
Section: -Sx -C 251mentioning
confidence: 99%